Auditory cortical stimulability in non habilitated individuals – An evidence from CAEPs - Hariprakash Palaniswami; Aju Abraham; Krishna Yerraguntla (Journal of Otology, 2022)
Objective: The effect of long term auditory deprivation on Cortical Auditory Evoked Potentials (CAEPs) especially in human models is not well explored. Hence, the current study was aimed to investigate the effects of long-term auditory deprivation and stimulability of auditory cortex in non habilitated congenitally deaf adolescents and adults using CAEPs. Methods and Results: A total of 27 non-habilitated congenitally deaf adolescents/adults with age and gender matched normal hearing adolescents/adults participated in the study. The congenitally deaf group was fitted with high gain hearing aids (first fit). Further, the CAEPs were recorded. The obtained CAEP components were assessed for group effect, source and topographical differences. The between group analysis for CAEP responses showed a significant difference only for P2 latency and amplitude. The source analysis revealed that, in the normal hearing group for CAEPs, the sources were within the temporal regions. However, in the congenitally deaf group, along with the temporal cortex, the bilateral prefrontal cortex also was activated. Conclusion: The findings revealed that it is possible to stimulate and evoke a matured CAEP response from a long deprived auditory system with adequate acoustic stimulation. The presence of CAEP responses is indicative of the functionality of the innate auditory pathway and the crossmodal plasticity in long auditory deprived individuals.